2023
DOI: 10.1111/jvim.16620
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of muscle stiffness in 37 dogs with concurrent naturally occurring hypercortisolism

Abstract: Background Severe muscle stiffness (SMS) in dogs with hypercortisolism (HC) is uncommon. Objectives To evaluate signalment, presentation, treatments, and long‐term outcomes of dogs with concurrent HC and SMS. Animals Thirty‐seven dogs. Methods Medical records of dogs with HC and concurrent SMS were recruited from 10 institutions. Clinical information, test results, therapeutic responses, and survival times were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…On the other hand, some cases in past studies indicated that remission of myotonia symptoms, especially those of the temporalis muscle, tends to be difficult. In a few past case reports, myotonia of the limbs did not improve despite trilostane treatment [ 9 , 13 , 15 , 19 ]; in this case, as well as in previous cases, no sufficient therapeutic effects were observed on myotonia. The reason for different treatment responses between trismus and myotonia of the extremities is not clear.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…On the other hand, some cases in past studies indicated that remission of myotonia symptoms, especially those of the temporalis muscle, tends to be difficult. In a few past case reports, myotonia of the limbs did not improve despite trilostane treatment [ 9 , 13 , 15 , 19 ]; in this case, as well as in previous cases, no sufficient therapeutic effects were observed on myotonia. The reason for different treatment responses between trismus and myotonia of the extremities is not clear.…”
supporting
confidence: 49%
“…Decreased mandibular range of motion has been reported in myotonia congenita [ 8 ]. There has been a report that the canine case with muscle stiffness with concurrent hypercortisolism exhibited difficulty in chewing and swallowing, but the details of the case are not available [ 9 ]. In the present case, the diagnosis of hyperadrenocorticism was based on clinical presentation, bilateral adrenal enlargement, and the cortisol level of the ACTH stimulation test.…”
mentioning
confidence: 99%